Pengaruh Variasi Fluida Pendingin Terhadap Laju Pendinginan Engine Yamaha Nmax - Ade Wahyu Nugroho; Muhammad Idris; Indra Hermawan; Iswandi Iswandi (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2022)
Radiator is a cooling system using fluid as a heat exchanger. How the radiator works by channeling the heat released by the motor engine is then absorbed by the radiator coolant fluid. The radiator device consists of a coolant inlet and engine outlet, a cooling fan mounted in front or behind the radiator, and coolant. Coolant in the radiator has a very important role in dissipating engine heat to the environment. In this study, I will analyze the different types of coolant variations, namely water, prestone antifreeze, Seiken, premix coolant DCK, and yamacoolant. on the cooling rate and radiator effectiveness using rotation variations of 1600, 3000,5000 rpm and measurement times of 1, 5, and 10 minutes on the Yamaha Nmax engine. The results of the research that have been carried out are the average heat transfer rate and the highest radiator effectiveness occur in the Yamacoolant type cooling fluid of 1.992kW and 0.726, the second highest occurs in the Prestone cooling fluid where the heat transfer rate value is 1.918kW and the radiator effectiveness is 0.652, then followed by Seiken where the heat transfer rate is 1.901kW and the radiator effectiveness is 0.634, then followed by DCK the heat transfer rate is 1.702kW and the radiator effectiveness is 0.592 and the smallest is experienced by mineral water where the heat transfer rate is 1.542kW and the radiator effectiveness is 0.501.